Address medical decisions, return‐to‐play guidelines. Issue 10 (January 2015) - Neal, Timothy; Quandt, Eric; Thornton, James; Anderson, Jeffrey
<x xml:space="preserve">Abstract</x> It's critical that your athletics department and institution empower your sports medicine staff and physicians to make all medical decisions based on their professional judgment about what's best for the long‐term well‐being of each student‐athlete. In fact, case law establishes the team physician as having the final say in student‐athlete medical clearance.